Modelling of friction stir welding for robotic implementation. (19th June 2006) - Crawford, Reginald; Cook, George E.; Strauss, Alvin M.; Hartman, Daniel A.
A three-dimensional numerical model is used to simulate the Friction Stir Welding (FSW) process using the computational fluid dynamics package 'FLUENT'. Two mechanical models: the Couette and the Visco-Plastic fluid flow models for Al-6061-T6 were simulated. The simulation results are compared to experimental data for Al 6061-T6 welded at high rotational (1500–5000 rpm) and travel speeds ranging from 11 to 63 ipm (4.66–26.7 mm/s) are presented. This paper examines the forces and torques associated with the FSW process with respect to considerations necessary for robotic implementation. It is shown that force control is an important requirement of robotic FSW.